KONDISI BURNOUT SISWA BERDASARKAN JENIS KELAMIN - Rudi; Aam Imaduddin (Journal of Innovative Counseling : Theory, Practice, and Research, 2021)
The purpose of this study was to determine the description of burnout in class XI students of SMA Negeri 1 Karangnunggal based on gender and program planning based on Solution Focus Brief Counseling. This study uses a quantitative descriptive method to reveal a picture of student fatigue. The population in this study were 321 students of class XI SMA Negeri 1 Karangnunggal, the technique in this study used saturated sampling by taking all members of the population as the sample. The results of this study in general, the burnout of class XI students of SMA Negeri 1 Karangnunggal included in the medium category with a frequency of 229 students (73.63%). The burnout dimensions of emotional exhaustion were highest and depersonalization was the lowest. Based on gender, there is no significant difference between male and female fatigue.